Pengaruh Kombinasi Bungkil Sawit Terfermentasi Dengan Natura Organik Dekomposer dan Ampas Tahu Terhadap Laju Pertumbuhan Maggot BSF (Hermetia illucens ) - Ivone Christiana; Maryani Maryani; Mohamad Rozik; Matling Matling; Yosua Lumbantoruan (Jurnal Akuakultur Sungai dan Danau, 2023)
BSF maggots (Hermetia illucens) also have quite high nutritional content, making BSF maggots able to be used as feed for fish. Maggot BSF works to convert organic waste into simpler biomass. Organic waste from agricultural waste is a medium for maggot enlargement that can be used as feed. Agricultural organic waste in Indonesia is available in quite large quantities. The types of waste that can be used as cultivation media are tofu waste and palm oil cake waste.  This study aims to determine the effect of the combination of fermented palm oil cake with natural organic decomposer and tofu waste on the growth rate of Maggot BSF (Hermetia illucens). The method used in this research is the experimental method using Completely Randomized Design (CRD). The factors studied were the combination of fermented palm oil cake with natural organic decomposer and tofu waste on the growth of Maggot BSF which consisted of 4 treatment levels, namely A (100% fermented palm oil cake); B (75% fermented palm oil + 25% tofu dregs); C (50% fermented palm oil + 50% tofu dregs); D (25% fermented palm oil + 75% tofu waste). Parameters observed were BSF maggot length and weight growth, digested feed conversion efficiency (ECD), waste reduction index (WRI), BSF maggot productivity.  Data used is Analysis of Variance (ANOVA) and to determine the best treatment using a follow-up test in the form of Duncan's test with a significance level of 5%. The results showed that the combination of fermented palm oil cake with different natural organic decomposers and tofu dregs had a significant effect on the productivity of BSF maggots. The best combination of fermented palm oil cake with natural organic decomposer and tofu waste on the growth rate of Maggot BSF is 100% fermented palm oil cake which has a significant effect when compared to other treatments.